Use of Social Media as E- Learning Media on the Understanding of Alifa Kids Kemang Sari Paud Students in the Period of March-June 2020 - Kristopo, Kristopo (Jurnal Multidisiplin Sahombu, 2025)
The rapid development of technology has significantly impacted the role of the internet and social media in society. Their use is no longer limited to connecting those far away or simply seeking information. Social media is now also being used for educational purposes, or e-learning . This study was conducted to determine how the use of social media as a learning medium impacts early childhood understanding. Interviews, questionnaires, observations, and literature review were used throughout the study. The goal was to assess the understanding of early childhood students during e-learning . The respondents in this study were 17 parents of students at Alifa Kids Kemang Sari Kindergarten. Each respondent was asked several questions related to the use of social media for e-learning as a learning medium for children in early childhood education. The results of processing respondent data show that the use of social media as an e-learning learning medium is not appropriate because the number of students who do not understand the material is greater than the number of students who understand the content of the material displayed on learning media via social media.